Controlling the anaphylatoxin C5a in diseases requires a specifically targeted inhibition - Riedemann, Niels Christoph; Wehling, Cyrill; Kirschfink, Michael (Clinical immunology, 2017)
The terminal complement split product C5a has been described as an important mediator in inflammatory diseases. C5a is generated upon cleavage of C5 and earlier research suggests that, besides the known C5 convertases formed upon activation of the complement pathways, various enzymes could activate C5 directly. We demonstrate that eculizumab effectively blocks C5 activation when mediated by C5-convertase formation, but fails to block C5a generation resulting from direct enzymatic cleavage by trypsin and thrombin. C5a generated by these enzymes is shown to be fully biologically functional and can be blocked by IFX-1, a specific monoclonal anti-human C5a antibody. We further report clinical cases of atypical hemolytic uremic syndrome (aHUS) and C3 Glomerulonephritis (C3GN) patients under treatment with eculizumab presenting substantially elevated C5a levels. Thus, blocking the C5 convertase mediated activation of C5 may not be efficient to control C5a-mediated effects in human disease and that a targeted approach is warranted.